Evaluation of a New and Simple Classification for Endoscopic Sinus Surgery. Issue 3 (October 2017) - Kanai, Kengo; Okano, Mitsuhiro; Haruna, Takenori; Higaki, Takaya; Omichi, Ryotaro; Makihara, Sei-ichiro; Tsumura, Munechika; Kariya, Shin; Hirata, Yuji; Nishizaki, Kazunori
Objective: In 2013, the Japanese Rhinologic Society proposed a simple classification for endoscopic sinus surgery (ESS). This classification consists of five procedures (type I, fenestration of the ostiomeatal complex, with uncinectomy and widening of the natural ostium; type II, single-sinus procedure, with manipulating the inside of the sinus; type III, polysinus procedure; type IV, pansinus procedure; type V, extended procedure beyond the sinus wall). The clinical relevance of this classification in chronic rhinosinusitis (CRS) and paranasal sinus cyst was evaluated. Study Design: A retrospective validation study. Methods: A total of 122 patients (195 sinuses) who underwent ESS in Okayama University Hospital in 2012 were enrolled. The relationships between the ESS classification and the clinical course, including the operation time, bleeding amounts during surgery and postoperative changes of olfaction, the computed tomography (CT) score, and nasal airway resistance were analyzed. Results: A total of 195 ESS procedures were classified into type I (n = 3), type II (n = 17), type III (n = 91), type IV (n = 82), and type V (n = 2). The major phenotypes of type II, III, and IV ESS were paranasal sinus cyst (68%), CRS without nasal polyps (77%), and CRS with nasal polyps (55%), respectively, and the difference was significant. The degree of ESS based on this classification was positively and significantly correlated with the operation time and bleeding amounts. As a whole, olfaction, CT score, and nasal airway resistance were significantly improved after surgery. The degree of improvement was similar between type III and type IV ESS. Conclusion: This simple classification for ESS reflected the perioperative burden of the disease.